Innovahub communication and outreach activities: Overview of communication strategy and materials for local stakeholders and farmer community engagement - Loon, Jelle van; Mena-Lopez, Georgina; Alarcón González, Francisco; Martínez, Jesús David; Arce, Daniela (Bioversity International and the International Center for Tropical Agriculture, 2023)
The communication strategy aims to engage stakeholders by showcasing the results and achievements made in the AgriLAC Resiliente regional initiative and, in particular, on advances related to the establishment of the Innovahubs across the region. This report details the overall strategy and includes an overview of all the communication and outreach materials developed over 2023. In the specific case of AgriLAC Resiliente, the communication of on-field actions and achievements by the technical implementation team is particularly relevant as its objective is to communicate the activities carried out through the Innovahubs and its local partners recognizing the effort and the commitment of the stakeholders involved at a regional level. Creating a sense of community around a common mission and acknowledge the activities of the Innovahub actors is an essential part to build ownership and participatory action within the AgriLAC regional initiative and that is what the community and outreach activities underline.